ANALISIS PENERAPAN KONSEP SISTEM MANAJEMEN BASIS DATA PADA PT. TELEKOMUNIKASI INDONESIA, Tbk. - Adillah Sofiyah Ananda; M. Difach Hazairin Nst; Syakira Rifdahayani Yoes (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
Developments in science and information technology are growing rapidly, making every company operating in the trade and services sector have to compete with other companies in order to continue to develop, and be able to gain competitiveness within a company. In this case, the application of the concept of a data-based management system will make the implementation run well. This research uses qualitative research using data collection methods through observation interviews and questionnaires taken based on primary and secondary data. The results of this research are that the implementation of a database management system within the Company will create effectiveness and efficiency within the company that is effective, wise and strategic as well as all resources within the Company (human resources, finance and technology) in producing competitive advantages and achieving goals. which are expected.